Growth and Yield of Shallot Plants with the Application of Sp-36 Fertilizer and Poc from Red Devil Fish - Manullang, Yedija; Damanik, Revandy; Sembiring, Mariani (Journal La Lifesci, 2025)
Shallots (Allium ascalonicum L.) are one of the horticultural commodities with high economic value and are needed by the community as food. Shallots also contribute to national inflation. Shallots become potential commodity to be developed in the region of North Sumatra, especially in the Toba region. One of the efforts to increase the growth and production of shallot plants can be done by applying SP-36 Fertilizer and Red Devil Fish Liquid Organic Fertilizer. This research aims to determine the best SP-36 and Red Devil Fish Liquid Organic Fertilizer, growth and production of shallots. The research was conducted from September to December 2023 in Lumban Silintong Village, Balige District, Toba Regency, North Sumatra with an altitude of ± 945 m above sea level. The design used was a factorial Randomized Group Design with three replications. The treatments studied were the first factor of SP-36 dose with four levels of treatment (0 (control), 112.5 Kg/Ha, 225 Kg/Ha, 337.5 Kg/Ha and the second factor was the dose of liquid organic fertilizer of red devil fish (0 (control), 3 g/plot, 5 g/plot). The results showed that the provision of SP-36 had a significant effect on the observed variable, namely the fresh weight of plants per plot. Giving Red Devil Fish Liquid Organic Fertilizer can significantly increase plant height, plant fresh weight per plot, plant fresh weight per sample, number of tubers per plot and tuber diameter.